Trade and the distribution of human capital - Spiros P. Bougheas; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2005)
We develop a two-country, two-sector model of trade where the only difference between the two countries is their distribution of human capital endowments. We show that even if the two countries have identical aggregate human capital endowments the pattern of trade depends on the properties of the two human capital distributions. We also show that the two distributions of endowments also completely determine the effects of trade on income inequality. Then, we prove that there are long-term gains from trade if the marginal utility of income is constant or as long as losers from trade are compensated by winners. Finally, we look at a simple majority voting model. It turns out depending on the distribution of human capital, autarky and free trade with and without compensation may be the outcome of majority voting.
Keywords: F1; 330; patterns of trade; income distribution; welfare; political economy; Außenwirtschaftstheorie; Humankapital; Zwei-Länder-Modell; Mehr-Sektoren-Modell; Wohlfahrtseffekt; Einkommensverteilung; Außenwirtschaftspolitik; Public Choice